EVALUATION OF THE ACCURACY OF USING TOPICAL ANTIBIOTICS IN SELF-MEDICATION FOR ACNE VULGARIS AT THE DENPASAR REGIONAL PHARMACY - Sutema, Ida Ayu Manik Partha; Mahayasa, Alma Lystia Savitri; Bakta, I Made (Journal Pharmaceutical Science and Application, 2023)
Background : One of the skin problems that are often experienced by teenagers today is acne. Acne vulgaris or acne is a chronic inflammatory disease of pilosebaceous follicles which is characterized by the formation of papules, pustules, or nodules. Purpose: This study aims to provide an accurate description of the use of topical antibiotics in acne vulgaris patients and to find out which drugs are often used as self-medication for acne vulgaris. Methods: This research is included in a descriptive research design. Data collection was done by direct observation and recorded on the checklist sheet for Acne Vulgaris patients who did self-medication at the pharmacy. Results: Judging from the evaluation of the accuracy of the use of topical antibiotics in AV patients at the Denpasar Regional Pharmacy, the results obtained were 53 patients, or 92.98% of patients included in the right indication group, 57 patients, or 100%, included in the right dose group, 54 patients or 94.74% included in the right group for the duration of administration, 57 patients or 100% were included in the appropriate time interval group for administration and 100% of patients were included in the side effect alert group. The accuracy of giving antibiotics, which is included in the category of inappropriate indications by 5.71% of respondents, and inappropriate duration of administration by 5.08% of respondents. The drugs used for AV therapy are Topical Retinoids, Mediklin Gel, Mediklin TR, and Erymed. The drug most often given by pharmacists is topical antibiotics, namely Mediklin TR from the Semisynthetic Lincosamide group, as much as 38.57%. Conclusion: There is still suitability for prescribing topical antibiotics in acne vulgaris seen from its severity. Keywords: Acne; Evaluation; Topical antibiotics